2001
DOI: 10.1046/j.1432-1327.2001.02325.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and heterologous expression of novel glucosyltransferases from tobacco cultured cells that have broad substrate specificity and are induced by salicylic acid and auxin

Abstract: Scopoletin is one of the phytoalexins in tobacco. Cells of the T-13 cell line (Nicotiana tabacum L. Bright Yellow) accumulate a large amount of scopoletin, also known as 7-hydroxy-6-methoxycoumarin, as a glucoconjugate, scopolin, in vacuoles. We report here the molecular cloning of glucosyltransferases that can catalyze the glucosylation of many kinds of secondary metabolites including scopoletin. Two cDNAs encoding glucosyltransferase (NtGT1a and NtGT1b) were isolated from a cDNA library derived from the toba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 34 publications
2
93
0
1
Order By: Relevance
“…NtGT2 was obtained by the screening of the tobacco cDNA library [22] using a fragment of the Perilla glucosyltransferase gene (3R4, [12]) containing the PSPG box.…”
Section: Screening and Sequencing Of Glucosyltransferase Genes A Parmentioning
confidence: 99%
See 3 more Smart Citations
“…NtGT2 was obtained by the screening of the tobacco cDNA library [22] using a fragment of the Perilla glucosyltransferase gene (3R4, [12]) containing the PSPG box.…”
Section: Screening and Sequencing Of Glucosyltransferase Genes A Parmentioning
confidence: 99%
“…Affinity-purified enzymes were used to determine substrate specificity and enzymatic parameters. The enzyme reaction for the determination of the substrate specificity of rNTGT2 using UDP-[ 14 C] glucose was performed as described previously [22]. For the reaction with the anthocyanin substrate, the enzyme was extracted using 50 mM Tris-HCl (pH 8.0) containing 10 mM 2-mercaptoethanol, according to Yamazaki et al [12].…”
Section: Screening and Sequencing Of Glucosyltransferase Genes A Parmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present investigation we have used site-directed mutagenesis, and domain swapping experiments between CaUGT2 and NtGT1b, to try to identify specific amino acids within the PSPG-box of CaUGT2 that control its catalytic function and substrate recognition properties. NtGT1b is a tobacco group E UGT which displays very little ability to glucosylate curcumin [24]. These experiments revealed that a single relatively non-conserved amino acid residue plays an important role in defining the catalytic activity of CaUGT2.…”
Section: Introductionmentioning
confidence: 98%